Validation of an integrated service model, Health-RESPECT, for older patients in long-term care institution using information and communication technologies: protocol of a cluster randomised controlled trial. Issue 10 (10th October 2020) - Choi, Jung-Yeon; Kim, Kwang-il; Kim, Hongsoo; Jung, Young-il; Oh, In-Hwan; Chun, Seungyeon; Kim, Gi-Soo; Lim, Jae-Young; Ko, Jin Young
Abstract : Introduction: There is an increased healthcare need to manage institutionalised older patients owing to the ageing population. To overcome substantial future challenges, the Health-RESPECT (caRE Systems for Patients/Elderly with Coordinated care using icT), a new information and communication technologies based integrated management service model, was developed to provide effective management, enable consultation with distant professionals and share medical information between acute care hospitals and long-term care institutions. Methods and analysis: A cluster randomised controlled trial will be conducted to examine the effectiveness of the Health-RESPECT in older patients with chronic diseases and their medical staff in charge. Intervention involves registration with simple comprehensive geriatric assessment, establishment of an individualised care plan for three chronic diseases (hypertension, diabetes and heart failure), medication and rehabilitation management, periodic video-conference and in-system assessment after intervention period. Primary outcomes are control levels of the three chronic diseases, adequacy of drug management and overall functional status. Patients will be assessed at before and after study period and 3 months after study ended. Analysis will be carried out with an intention-to-treat principle. In addition to evaluate intervention effects, clinical usability and economic evaluation will be assessed. Ethics and dissemination: The study protocol was reviewed and approved by the Seoul National University Bundang Hospital Institutional Review Board. Study findings will be published in peer-reviewed journals. Trial registration number: KCT0004360.